Razzismo nel calcio italiano: due casi a confronto - Francesco Annunziata (Culture e Studi del Sociale)
This work is based on a well-known phenomenon and deep-rooted in the sport: racism to players as a form of aggression. Starting from the quotation of the Mancino law n. 205 of 25 June 1993 and the regulations over the years have brought changes with the inclusion of DASPO, you may notice that in the twenty years after the introduction of this legislation, the situation remains similar. The two events I considered discriminatory, date back to Jan-uary 3 and May 12 of 2013, where the protagonists, respectively Boateng and Balotelli, two players of the same Italian team: AC Milan. To unite the protagonists/victims of the event is not only the profession or belonging to the same team (an element that this could justify a territorial discrimination), but the same skin color. To be able to explore the episodes in question, I have made use of newspaper articles published by the Gazzetta dello Sport and Corriere dello Sport in the week following the event. Through lessicometrica analysis, car-ried out with the support of Lexico3 software, I was able to examine specifically the two cases in question.